Practicing positive CBT from reducing distress to building success - Bannink, Fredrike (Chichester, West Sussex ; Hoboken : Wiley-Blackwell, 2012)
'Practicing Positive CBT: From Reducing Distress to Building Success reveals a new therapeutic approach that combines traditional CBT with Positive Psychology and Solution-Focused Brief Therapy. By shifting the focus of therapy from what is wrong with clients to what it right with them and from what is not working to what is, Positive CBT creates a more optimistic process that empowers clients and therapists to flourish. Increases client motivation and collaboration; allows therapeutic outcomes to be achieved in shorter timeframes and in a more cost-effective way Covers theory and applications, and provides a wide range of stories, exercises and case studies The author has a uniquely broad knowledge and experience as a therapist and trainer of CBT, PP, and SFBT'--
Machine generated contents note: pt. I THEORY -- 1. What is CBT? -- Introduction -- CBT Techniques -- Empirical Evidence -- 2. What is Positive CBT? -- Introduction -- Shortcomings of die Problem-Solving Paradigm -- Story 2.1 How to Not Be Unhappy -- Towards a Strengths and Solutions Paradigm -- Notes on Learning Theory -- Story 2.2 I Can Choose -- Changing Role of the Therapist -- Differences Between Traditional CBT and Positive CBT-An Overview -- Story 2.3 Looking for Problems? -- 3. Possibilities of Positive CBT -- Introduction -- What is Positive in Traditional CBT? -- Possibilities of Positive CBT -- 4. Two Positive Sources -- Introduction -- Source 1 Positive Psychology -- Story 4.1 The Power of Positive Emotions -- Source 2 Solution-Focused BriefTherapy -- Story 4.2 Do Something Different for a Change -- Story 4.3 Working from the Future Back -- Short Comparison Between Positive Psychology and Solution-Focused BriefTherapy -- Empirical Evidence -- Neuroscience -- Story 4.4 The Drip System -- The Body -- pt. II APPLICATIONS -- 5. Enhancing the Therapeutic Alliance -- Introduction -- Building a Positive Alliance -- Offering Acknowledgment -- Story 5.1 Acknowledging the Problem -- Enhancing Hope -- Story 5.2 The Archer -- Story 5.3 The Power of Hope -- Reinforcing Strengths and'What Works' -- Enhancing Cooperation -- Story 5.4 Misery I Love You! -- Story 5.5 Everybody Somebody, Anybody, and Nobody -- 6. Assessment -- Introduction -- Case Conceptualization -- Assessing Goals -- Story 6.1 Top Performers -- Assessing Problems, Complaints, and Constraints -- Assessing Strengths and Resources -- Assessing Progress, Motivation, Hope, and Confidence -- Story 6.2 At the Car Wash -- Assessing Motivation to Change -- Positive Self-monitoring -- Positive Functional Behavior Analysis -- 7. Changing the Viewing -- Introduction -- Acknowledging Feelings and the Past -- Changing What the Client is Paying Attention to -- Story 7.1 Finding the'Bright Spots' -- Story 7.2 The Dog I Feed Most -- Story 7.3 Shake it Off and Step Up -- Focusing on What the Client Wants in the Future -- Challenging Unhelpful Beliefs -- Using a Spiritual Perspective -- 8. Changing the Doing -- Introduction -- Story 8.1 For a Change Do Something Different -- Changing Repetitive Patterns -- Story 8.2 Sail Away From the Safe Harbor -- Noticing What the Client is Doing When Things are Going Better -- Story 8.3 Chocolate-chip Cookies -- 9. Changing the Feeling -- Introduction -- Reducing Negative Emotions -- Building Positive Emotions -- Balancing Positive and Negative Emotions -- Story 9.1 Consider a Sail-boat -- Story 9.2 The Nun Study -- Positive Emotions in the Medical Setting -- 10. Homework Assignments -- Introduction -- General Suggestions -- Basic Homework Assignments -- Self-monitoring -- Behavioral Experiments -- Routine Outcome Measurement -- Story 10.1 Brilliant Insights -- Reflecting on the Session -- 11. Subsequent Sessions -- Introduction -- Progress -- Behavior Maintenance -- Failures -- Story 11.1 Ten Million Dollars Lost -- Concluding Therapy -- 12. Role of the Positive CBT Therapist -- Introduction -- Watering the Flowers -- Role of the Positive CBT Therapist -- Supertherapists -- Easy and Fun -- The Alliance Revisited -- Microanalysis -- Benefits for Therapists -- pt. III MORE APPLICATIONS -- 13. Positive CBT with Couples and Groups -- Introduction -- Positive CBT with Couples -- Story 13.1 The Norway Feedback Project -- Positive CBT with Groups -- 14. Positive CBT with Children and Families -- Introduction -- Positive CBT with Children -- Story 14.1 Little Squid -- Positive CBT with Families -- Transcultural Positive CBT -- 15. Positive CBT in the Workplace -- Introduction -- Positive CBT in a Team -- Story 15.1 We Can Learn From Geese -- Positive CBT in an Organization -- Story 15.2 Swarm Intelligence -- Story 15.3 What You Give is What You Get -- 16. Positive CBT and the Future -- Introduction -- Research -- Training -- 17. FAQ -- Introduction -- 20 Questions and Answers -- Epilog -- Story: On the Other Side.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Cognitive therapy; Positive psychology; Cognitive Therapy; PSYCHOLOGY -- Clinical Psychology; Cognitive therapy; Positive psychology; Electronic books; Electronic books